2019
DOI: 10.1111/pedi.12856
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinically relevant dysglycemia phenotypes based on continuous glucose monitoring data from youth with type 1 diabetes and elevated hemoglobin A1c

Abstract: Background/Objective: To identify and characterize subgroups of adolescents with type 1 diabetes (T1D) and elevated hemoglobin A1c (HbA1c) who share patterns in their continuous glucose monitoring (CGM) data as "dysglycemia phenotypes."Methods: Data were analyzed from the Flexible Lifestyles Empowering Change randomized trial. Adolescents with T1D (13-16 years, duration >1 year) and HbA1c 8% to 13% (64-119 mmol/mol) wore blinded CGM at baseline for 7 days. Participants were clustered based on eight CGM metrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In the stratification of T2DM, however, the use of CGM is quite limited. In adolescents with type 1 diabetes, Kahkoska et al 11 identified three dysglycaemia clusters based on CGM data, which displayed a significant difference in the progression of HbA1c over 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the stratification of T2DM, however, the use of CGM is quite limited. In adolescents with type 1 diabetes, Kahkoska et al 11 identified three dysglycaemia clusters based on CGM data, which displayed a significant difference in the progression of HbA1c over 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing studies focused on patient clustering have primarily utilized conventional CGM metrics recommended by international consensus rather than delving into the raw data. [10][11][12] It is crucial to note that widely used CGM metrics, such as time in range (TIR) and coefficient of variation (CV), primarily capture statistical characteristics and overlook the time-series nature of CGM data. Effectively interpreting the extensive data generated by CGM remains a critical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Data collected with CGM have also provided an important tool for testing the feasibility and effectiveness of insulin delivery systems, insulin treatments, adjunctive diabetes medications, T1D screening, new glucose monitoring systems, algorithms for the promotion of improved glycemic control, sensor-augmented therapy algorithms, and closed-loop systems ; diabetes alert dogs [92]; education programs aimed at improving impaired hypoglycemia unawareness, daily therapy decisions, and cardiovascular health [93][94][95]; and use of glucose sharing data with others [96]. This technology has also been used to assess the relationship between continuous glucose measures and other diabetes-related outcomes, including long-term glycemic control, dysglycemia [97,98], future T1D diagnosis or dysglycemia in preclinical youth [99][100][101], HbA 1c [102][103][104][105], C-peptide [102], insulin sensitivity [106], severe hypoglycemia [107], time in target range [108][109][110], glucose variability [109][110][111][112][113], detection of hypo-or hyperglycemia [108][109][110][114][115][116], glycated albumin [104], fructosamine [104], and 1,5-anhydroglucitrol [104]. Furthermore, CGM has been used to determine the relationship between continuous glucose measures and other medical outcomes, including body composition [117], markers of inflammation [118], cardiovascular health …”
Section: Using Cgm To Measure Outcomesmentioning
confidence: 99%
“… 12 13 By dividing the complete CGM curve into segments, Hall and colleagues 12 found three different fluctuation modes of CGM, and the frequencies of the three modes in individuals without diabetes, patients with pre-diabetes and patients with diabetes were finally found to be different. Kahkoska and colleagues 13 used eight CGM features to identify new subgroups of type 1 diabetes. Three subgroups showed significant differences in glycated hemoglobin A1c (HbA1c).…”
Section: Introductionmentioning
confidence: 99%
“…Three subgroups showed significant differences in glycated hemoglobin A1c (HbA1c). 13 The problem of using CGM indices to stratify patients with type 2 diabetes among different categories needs to be discussed further.…”
Section: Introductionmentioning
confidence: 99%